MORPHOLOGICAL CHANGES OF KIDNEYS OF RATS IN CONDITIONS OF CELLULAR DEHYDRATION ON POSTRAVMATYCHNOYI BACKGROUND OF TIBIA REGENERATION - Кіптенко, Л.І.; Vasko, L.; Kortinska, A.; Бумейстер, В.І.; Масленко, А.О. (World of Medicine and Biology, 2014)
On the 21st day the fibrous capsule in specimens is hardly evident. Perivascular lymphoid infiltrates are sometimes observed on histological preparations. There is a progressive ischemia of renal glomeruli. Renal vessels at all levels are full of blood, arterioles are in a state of spasm. Conclusions. Overall, in terms of cellular dehydratation frank changes in parenchymal organs occur on the 14th day. Thus, morphological changes of kidneys while microscopic examination occur in reducing the content of blood, ischemia of tissue, with increasing time of observation, on the background of arteriospasm of inrarenal vessels thinning of renal capsule and the fluctuation of the size of renal capsules to the big.
Keywords: kidneys; dehydratation; posttraumatic regeneration